Application of artificial intelligence in learning activities of students at Thai Nguyen University of Sciences currently - Bui Trong Tai (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2025)
Artificial intelligence (AI) in education has been researched and applied since the 70s of the twentieth century. With the support of the internet, AI is increasingly widely applied in almost every country in the world. From the theoretical and practical basis of some countries on the application of AI in education (AIED), the author researches and clarifies the current status of AI applications in the learning activities of students at the Thai Nguyen University of Sciences. Using document research and survey methods, research results show that students apply AI in learning activities, specifically: using AI in homework and essays; Application in slide design, graphics, images used in learning; Using AI in translation for learning; using AI in teamwork; Using AI in searching documents for learning and using AI in data analysis and scientific research. From there, the authors discuss the positive and negative effects, as well as solutions to increase the positive effects and minimize the negative effects of AI in the learning activities of students at Thai Nguyen university of Sciences today. Code: 24052901